Vitamin A status of HIV-infected adults in South Africa - Visser, Marianne Emilie (Centre for Infectious Disease Epidemiology and Research (CIDER), 2018)
Introduction: Several studies in developed countries such as the USA have reported low serum or plasma vitamin A levels in adults with HIV disease. Limited data suggests that HIV-infected adults from developing countries show even lower vitamin A levels. Factors that contribute to a low vitamin A status include a poor intake, malabsorption and repeated episodes of infections resulting in a decreased hepatic mobilisation of vitamin A during the acute phase response, an accelerated utilisation of vitamin A or increased urinary losses of vitamin A. Aim: To determine the vitamin A status of HIV-infected adults without major active opportunistic infections with WHO clinical stages 1 to 4 HIV-infection. Methods: One hundred and thirty-two HIV-positive patients were included in a cross-sectional study at the outpatient clinic at Groote Schuur Hospital. Exclusion criteria included current use of multivitamin or vitamin A supplements, pregnancy, pyrexia (> 38 °C) and patients who had received TB treatment for less than 12 weeks. We obtained data on demographic characteristics, weight and height, CD4 lymphocyte levels, CD4:CD8 ratio, full blood count and plasma levels of retinal, retinal-binding protein, zinc and CRP. Results: The sample consisted of 51, 48 and 33 patients with WHO Stage 1/2, 3 and 4 HIV-infection, respectively. The proportion of patients with borderline vitamin A levels (< 30 μg/dl) for male and female subjects increased linearly across clinical stage categories. Thirty nine percent (20/51) of patients with early disease, 48% (23/48) with Stage 3 HIV-disease and 79% (26/33) of patients with AIDS showed a borderline vitamin A status (p < 0.001). Plasma retinal status was associated with CD4 lymphocyte levels (r=0.27; 95% Cl: 0.1-0.43) and the CD4:CD8 ratio (r=0.33; 95% Cl: 0.1 ;0.42). Only one subject demonstrated CRP levels > 100 mg/l. Seventy seven percent (39/51) of patients with early disease had CRP levels < 10 mg/l, compared to 52% (25/48) and 58% (19/33) of patients with stage 3 and 4 HIV disease. CRP levels were divided according to 3 categories: < 10 mg/l, 10-40 mg/l and > 40 mg/l. The median retinal level of patients with CRP levels> 40 mg/l (n=7) was 16.8 μg/l versus 27.3 μg/l and 30.2 μg/l in the other two categories (p < 0.05). A similar relationship between CRP and plasma zinc levels was observed, although not significant (p < 0.1). Multivariate analysis revealed that a borderline retinal status was independently associated with a 3-fold increase (95%CI: 2-5.6) in the risk of having stage 4 disease or AIDS after adjusting for CD4 lymphocyte count or the CD4:CD8 ratio, haemoglobin, plasma zinc and body weight. Conclusions: Patients with advanced disease are more likely to have a borderline vitamin A status in the absence of opportunistic infections. The majority of patients with symptomatic disease had mildly raised CRP levels, possibly reflecting HIV-viral activity. CRP levels were associated with low retinal levels only in a small number of subjects, possibly indicating the presence of underlying infection, despite the clinical review of our data. Although our data indicates an independent relationship between retinal levels and advanced disease, the cross-sectional design precludes causal inferences about this association.